KONTROVERSI AYAT ESKATOLOGI DALAM AL-QUR’AN PERSPEKTIF ORIENTALIS - Sona Hafadzah , Ahmad; Iman, Ainul (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This study aims to analyze the forms of controversies of eschatological verses found in the quran from an orientalist perspective in terms of language and to identify the factors that influence the existence of these controversies, as well as the implications for the authenticity of the Qur'an. The result of this study is that there are several forms of vocabulary that contain discussion of eschatology in the Qur'an and are influenced by the Syro-Aramaic language as claimed by Luxenberg. There is a Jewish cultural influence in Abraham Geiger's view, as well as a form of language style influenced by Christian traditions according to Noldeke. The existence of these forms of language style is inseparable from the factors that influence it, be it the interaction of Arabs with non-Arabs and so on, which many orientalists describe. This causes the entry of foreign languages which are indicated to be contained in the Qur'an. So that it has implications for doubts about the originality of the Qur'an by orientalists. The conclusion is, even though there are similarities in foreign language styles in the Qur'an, this does not affect the authenticity of the Qur'an, instead it shows that the Qur'an is the closing book and complements the previous books and is a source the spirit of monotheism for Muslims.